Modelling Thermo-Electro-Mechanical Effects in Orthotropic Cardiac Tissue (Communications in Computational Physics, 2020)
In this paper we introduce a new mathematical model for the active contraction of cardiac muscle, featuring different thermo-electric and nonlinear conductivity properties. The passive hyperelastic response of the tissue is described by anorthotropic exponential model, whereas the ionic activity dictates active contraction incorporated through the concept of orthotropic active strain. We use a fully incompressible formulation, and the generated strain modifies directly the conductivity mechanisms in the medium through the pull-back transformation. We also investigate theinfluence of thermo-electric effects in the onset of multiphysics emergent spatiotemporal dynamics, using nonlinear diffusion. It turns out that these ingredients havea key role in reproducing pathological chaotic dynamics such as ventricular fibrillation during inflammatory events, for instance. The specific structure of the governingequations suggests to cast the problem in mixed-primal form and we write it in termsof Kirchhoff stress, displacements, solid pressure, dimensionless electric potential, activation generation, and ionic variables. We also advance a new mixed-primal finiteelement method for its numerical approximation, and we use it to explore the properties of the model and to assess the importance of coupling terms, by means of a fewcomputational experiments in 3D.
Keywords: Cardiac electromechanics; orthotropic active strain; thermo-electric coupling; scroll wave propagation; numerical simulations.